Interferon-β and interleukin-6 exert opposing effects on Foxp3 acetylation to control regulatory T cell induction - Ningoo, Mehek; Fueyo-González, Francisco; Gisbert-Vilanova, Cayetana; Espinar-Barranco, Laura; Marjanovic, Nada; Fribourg, Miguel (Frontiers in Immunology, 2025)
Cytokines are key soluble signaling molecules that regulate immune responses. With the advent of therapies that selectively target cytokines and cytokine receptors, understanding the molecular mechanisms underpinning how immune cells integrate multiple cytokine signals has become a critical challenge in immunology. However, the pleiotropic nature of cytokines makes it difficult to decipher their precise contributions in various contexts. Here, we used an integrated experimental and computational approach to investigate the combined effect and interplay between the pro-inflammatory cytokine interleukin-6 (IL-6) and interferon-beta (IFNβ), also a pro-inflammatory cytokine with potent antiviral properties, in modulating regulatory T cell (Treg) induction. Our studies reveal that, in contrast with its pro-inflammatory role in innate immune responses, IFNβ can counteract the well-described inhibitory effect of IL-6 on Treg induction. Mechanistically, we demonstrate that IFNβ and IL-6 signal independently to promote opposing effects on the acetylation of Foxp3, an essential transcription factor governing Treg differentiation, stability, and function. We further show that this mechanism is conserved in both murine and human T cells, highlighting the broad relevance of this finding in immune regulation. These results have important implications for the numerous contexts in which IFNβ and IL-6 co-exist, including viral infection, transplantation, and autoimmune disease.